Hydrological Effects on Relationships Between N-15 of River Nitrate and Land Use in a Rural River Basin, Western Japan - Ide, J.; Somura, H.; Nakamura, T.; Mori, Y.; Takeda, I.; Nishida, K. (Wiley, 2015)
This study aimed to examine how the relationship between N-15 of nitrate (N-15(NO3)) in rivers and land use within a river basin changes with varying hydrological conditions. This information would aid in identifying the dominant source contributing to increased nitrate concentrations in rural rivers. For this, N-15(NO3) in river water was investigated monthly in the five subbasins of the Hii River basin (area: 911km(2)), western Japan, for 1year and 3months. There were significant correlations (p<0.05) between N-15(NO3) and the land-use ratio (i.e. ratios of forested, agricultural and residential areas in a subbasin) for the majority of the observation days, indicating that N-15(NO3) reflected land use within the basin. N-15(NO3) ranged from +1.4 parts per thousand to +8.5 parts per thousand and was lower in a subbasin with a higher forested area ratio. We found that the absolute value of the regression slope of the relationship between N-15(NO3) and the land-use ratio decreased with increasing river discharge. This finding demonstrates that differences in N-15(NO3) among subbasins with different land-use compositions became smaller under higher flow conditions. Because N-15(NO3) decreased with increasing river discharge, the small absolute value of the regression slope under high flow conditions indicates that forested areas could be the dominant source of river nitrate during high flows in all subbasins investigated regardless of land-use composition. The results suggest that forested areas make a large contribution to the increase in nitrate concentration in downstream rivers during high flows, because the nitrate concentration increased with increasing river discharge.
Keywords: anthropogenic and natural sources; diffuse pollution; hilly and mountainous area; nitrogen; stable isotope